Industrialization and Occupational Mortality in France Prior to 1914 - Lewchuk, Wayne (Explorations in Economic History, 1991)
Did workplace characteristics, such as the degree of mechanization or the level of managerial control, systematically influence occupational mortality rates in France at the beginning of the 20th century? Data from an early 20th-century study of occupational mortality in France lead us to conclude that long hours of work, under conditions where labor had limited control of the pace of work, represented the most serious occupational risk facing early French workers. The effect of long hours of work on mortality dwarfed the impact of either mechanization or size of establishment.